The Consignment of Indonesian Migrant Workers in Saudi Arabia and Its Resilience: Examining the Impacts of Indonesia’s Moratorium Policy (2011-2015). - Witri Elvianti; Jihan Djafar Sidik (Department of International Relations, Universitas Andalas, 2018)
Although Indonesian migrant workers in Saudi Arabia, particularly at informal sectors, have exponentially increased in last decades, most of the time, they have also faced several constraints such as the lack of protection that supposedly addressed by the Government of Indonesia (GoI) through Indonesian embassy, limited numbers of regulations that could protect the Indonesian migrant workers from the Government of Saudi Arabia, due to the absence of Memorandum of Understanding between the two countries. Such complex circumstances made the position of Indonesian migrant workers worsened due to their disability in gaining their rights. In the implementation process, the GoI’s protection has not been maximal in ensuring the safety of their workers abroad. The situation reached the peak when the death penalty for Ruyati binti Satubi was conducted by Government of Saudi Arabia without any initiatives informing Indonesian authority prior to the execution. Consequently the former President of Indonesia, Susilo Bambang Yudhoyono, declared a moratorium policy during the cabinet meeting on June 23, 2011, in order to improve the protection mechanism of Indonesian migrant domestic workers. In milieu of this issue, the researchers attempted at analyzing the impacts of such a policy. The analysis was based on national interest theory. In the context of Indonesian migrant domestic workers, this study came to argue that the moratorium policy could be seen as a manifestation of political commitment from Indonesia’s government perceiving the protection of Indonesian migrant workers is high in the list.